2009
DOI: 10.1186/1757-1626-2-7138
|View full text |Cite
|
Sign up to set email alerts
|

Upper-lip laser frenectomy without infiltrated anaesthesia in a paediatric patient: a case report

Abstract: Labial frenectomy is a common surgical procedure in the field of oral surgery. Labial frenectomy is a procedure usually done for orthodontic reasons. The role of laser surgery in the oral cavity is well established. The use of diode laser frenectomy without infiltrated anaesthesia is currently under investigation. Needle-less oral surgery, without infiltrated anaesthesia, is a novel situation in paediatrics with paramount importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 7 publications
2
21
0
7
Order By: Relevance
“…[17][18][19][20] Other several studies evaluated that to compare lasers in the soft tissue surgical procedures with conventional surgery in young patients during orthodontic treatment but in this study we evaluated and compared this two type surgical procedure in adult patients needing cosmetic smile position gingivectomy. 9,12,16,21 Therefore, there is no study in the literature similar to this study.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…[17][18][19][20] Other several studies evaluated that to compare lasers in the soft tissue surgical procedures with conventional surgery in young patients during orthodontic treatment but in this study we evaluated and compared this two type surgical procedure in adult patients needing cosmetic smile position gingivectomy. 9,12,16,21 Therefore, there is no study in the literature similar to this study.…”
Section: Discussionmentioning
confidence: 79%
“…[17][18][19] Most of the patients in test group, surgery were performed without anesthesia but almost all patients in control group were injected infiltrative anesthesia. 20,21 Conventional surgical have caused some problems like: surgical trauma, bleeding during surgery, postoperative pain and swelling, low satisfaction of patient. These problems can handle more easily with lasers.…”
Section: Discussionmentioning
confidence: 99%
“…6 Regarding to frenectomy procedure, the decrease in pain, bleeding and scar formation provided by laser make laser more desirable than conventional surgery. 5,10 Akpinar et al demonstrated that…”
Section: Discussionmentioning
confidence: 99%
“…In dentistry, it is generally preferred for resective gingival/mucosal surgeries such as frenectomy, gingivectomy, gingivoplasty and epulis fissuratum [9][10][11][12][13] , and oral lesions such as leukoplakia, oral lichen planus and mucous membrane pemphigoid. [13][14][15] Medical applications of laser surgery involve treatment of vascular lesions such as hemangioma and telangiectasia.…”
mentioning
confidence: 99%
“…The use of electro surgery and lasers has also been proposed for frenectomy [4][5][6][7][8][9]. Researchers have advocated the use of an electrocautery probe due to its efficacy and due to the safety of the procedure, the mild bleeding and the absence of postoperative complications.…”
Section: Dentistry Sectionmentioning
confidence: 99%